Safety and efficacy of zilucoplan in patients with generalised myasthenia gravis (RAISE): a randomised, double-blind, placebo-controlled, phase 3 study. Issue 5 (May 2023) - Howard, James F; Bresch, Saskia; Genge, Angela; Hewamadduma, Channa; Hinton, John; Hussain, Yessar; Juntas-Morales, Raul; Kaminski, Henry J; Maniaol, Angelina; Mantegazza, Renato; Masuda, Masayuki; Sivakumar, Kumaraswamy; et al.
Summary: Background: Generalised myasthenia gravis is a chronic, unpredictable, and debilitating rare disease, often accompanied by high treatment burden and with an unmet need for more efficacious and well tolerated treatments. Zilucoplan is a subcutaneous, self-administered macrocyclic peptide complement C5 inhibitor. We aimed to assess safety, efficacy, and tolerability of zilucoplan in patients with acetylcholine receptor autoantibody (AChR)-positive generalised myasthenia gravis. Methods: RAISE was a randomised, double-blind, placebo-controlled, phase 3 trial that was done at 75 sites in Europe, Japan, and North America. We enrolled patients (aged 18–74 years) with AChR-positive generalised myasthenia gravis (Myasthenia Gravis Foundation of America disease class II–IV), a myasthenia gravis activities of daily living (MG-ADL) score of least 6, and a quantitative myasthenia gravis score of at least 12. Participants were randomly assigned (1:1) to receive subcutaneous zilucoplan 0·3 mg/kg once daily by self-injection, or matched placebo, for 12 weeks. The primary efficacy endpoint was change from baseline to week 12 in MG-ADL score in the modified intention-to-treat population (all randomly assigned patients who received at least one dose of study drug and had at least one post-dosing MG-ADL score). Safety was mainly assessed by the incidence of treatment-emergent adverse events (TEAEs) in all patients who had received at least one dose of zilucoplan or placebo. This trial is registered at ClinicalTrials.gov, NCT04115293 . An open-label extension study is ongoing (NCT04225871 ). Findings: Between Sept 17, 2019, and Sept 10, 2021, 239 patients were screened for the study, of whom 174 (73%) were eligible. 86 (49%) patients were randomly assigned to zilucoplan 0·3 mg/kg and 88 (51%) were assigned to placebo. Patients assigned to zilucoplan showed a greater reduction in MG-ADL score from baseline to week 12, compared with those assigned to placebo (least squares mean change −4·39 [95% CI –5·28 to –3·50] vs −2·30 [–3·17 to –1·43]; least squares mean difference −2·09 [−3·24 to −0·95]; p=0·0004). TEAEs occurred in 66 (77%) patients in the zilucoplan group and in 62 (70%) patients in the placebo group. The most common TEAE was injection-site bruising (n=14 [16%] in the zilucoplan group and n=8 [9%] in the placebo group). Incidences of serious TEAEs and serious infections were similar in both groups. One patient died in each group; neither death (COVID-19 [zilucoplan] and cerebral haemorrhage [placebo]) was considered related to the study drug. Interpretation: Zilucoplan treatment showed rapid and clinically meaningful improvements in myasthenia gravis-specific efficacy outcomes, had a favourable safety profile, and was well tolerated, with no major safety findings. Zilucoplan is a new potential treatment option for a broad population of patients with AChR-positive generalised myasthenia gravis. The long-term safety and efficacy of zilucoplan is being assessed in an ongoing open-label extension study. Funding: UCB Pharma.